Effectiveness of early interventions for substance-using adolescents: findings from a systematic review and meta-analysis - Carney, Tara (BioMed Central, 2012)
BACKGROUND: Information on the impact of available interventions that address adolescent substance use and delinquency can inform investment choices. This article aims to identify and evaluate early interventions that target adolescent substance use as a primary outcome, and criminal or delinquent behaviours as a secondary outcome. METHOD: A systematic review of early interventions for adolescent substance use and behavioural outcomes was conducted. RESULTS: We identified nine studies using specific search strategies. All but one of the studies reported the use of brief intervention strategies. Only seven studies contained information which allowed for the calculation of an effect size, and were therefore included in the meta-analysis. The overall effect size for all outcomes combined was small but significant (g = 0.25, p < 0.001). The overall outcome for substance use was also small but significant (g = 0.24, p < 0.001). For studies with behavioural outcomes, the overall effect size reached significance (g = 0.28, p < 0.001). In general, subgroup analysis showed that individual interventions with more than one session had a stronger effect on the outcomes of interest. CONCLUSIONS: Early interventions for adolescent substance use do hold benefits for reducing substance use and associated behavioural outcomes. Interventions are most promising if delivered in an individual format and over multiple sessions. One intervention in particular had large effect sizes. As all the interventions were tested in developed countries, further testing is needed in low- and middle-income countries where there is a lack of research on evidence-based interventions for adolescent risk behaviours. Additional recommendations for policy and practice are provided in this paper.